(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2023)
In the article, the dynamics of the development of the fruit and vegetable sector in the republic in the conditions of digitization of the economy, the statistical indicators of the results achieved in the sector, the econometric models of the gross yield of fruit and vegetable products and the factors that strongly affect it are made, and correlation-regression analysis methods are used. economic indicators were thoroughly analyzed and forecasted, and practical recommendations and suggestions were given.